Recent Trends in Social Media Marketing Strategy - Wayan Sri Maitri; Suherlan Suherlan; Riyan Dwi Yulian Prakosos; Agus Dedi Subagja; Abu Muna Almaududi Ausat (Jurnal Minfo Polgan, 2023)
The development of technology and the internet has changed the way companies interact with their consumers. Social media marketing has become one of the increasingly important aspects of a company's marketing strategy. This study aims to analyse the current trends in social media marketing strategies. The focus of this study is primarily qualitative. Methods for gathering data include paying close attention to detail while viewing and recording data, and then using analytical techniques such as data reduction, visualisation, and inference to draw conclusions. The study arrived at the conclusion that current trends in social media marketing strategies include the use of video content, collaboration with influencers, the use of stories, the use of AR and VR technologies, content personalisation, UGC, audience engagement and responsiveness, the use of data and analytics, data management and privacy, and the ability to adapt to changing trends and user behaviour. Effective social media marketing strategies capitalise on these trends to expand reach, increase brand awareness and build strong relationships with audiences.